Perceptions of sex offenders with intellectual disability: a comparison of forensic staff and the general public - Steans, Jennifer; Duff, Simon (Wiley, 2018)
Background. Existing literature suggests that individuals with intellectual disability are not always held accountable for their actions and forensic staff are unlikely to report their sexually harmful behaviour.